Diseño de un sistema de control interno para la empresa mara Ltda. de la ciudad de Tunja (2023)
The present study focuses on the design of an internal control system based on the COSO Model for the treasury and operational areas in the construction company Mara Ltda. in the city of Tunja.The case study is descriptive, developed under an inductive method and a qualitative approach